ICONICITY IN THE BINOMIALS OF THE GLORIOUS QURAN: AL-BAQARAH SURA AS A CASE STUDY - Hazem, Ali Hussein; Salman, Zahraa Muharam; Kanaan, Muhammad Hamza (Universitas Islam Negeri Ar-Raniry, 2023)
This study investigates evidence for the existence of iconicity as a processing strategy in Quranic discourse. It is argued here that the Muslim’s most glorious book, the Quran, is an excellent source of morphosyntactic iconicity in the Arabic language. The hypothesis was tested by analysing sixty-six binomials from Al-Baqarah Sura within a synthetic model based on an extension of Givón’s 1984 model of iconicity. The findings show that some of the sampled iconic binomials accord with these principles, while others are iconic with regard to the human perceptual system. This result challenges Saussurian arbitrariness and lends support for the view that some aspects of language are iconic. Furthermore, iconic binomials are richly manifested in Quranic lexicon and discourse. This is because they are part of the rhetoric of Quran. Allah has created everything in pairs: night and day, death and life, sun and moon, paradise and hell, etc. These pairs express such rhetorical functions as revealing situation, warning, promising, inhibition, specification, etc. They also express Allah’s intention in motivating people to make a balance between benefits and problems of each pair. The role played by iconic binomials can be easily tested by removing some of them from the suras of Quran and asking what happens then. On such cases, the Quranic rhetoric is distorted rather than unites. Above all, such binomials are cross linguistics, they are universal since they are found in all languages. This conclusions challenges Sapir-Worf hypothesis and lends support to an assumption of a minimal universality of linguistic interactions.